The Impact of Traditional Art on Developing Visual Literacy and Creativity in Students - Nasulloyeva Sarvinoz Komiljon qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article examines the impact of traditional art on developing visual literacy and creativity in students. It emphasizes the integration of national and cultural art forms in visual arts lessons to enhance students’ artistic skills, aesthetic appreciation, and creative thinking. The study discusses practical, interactive, and project-based pedagogical approaches that enable students to apply traditional artistic elements in modern visual art projects while connecting with cultural heritage.